Study of maternal and fetal outcomes in patients with gestational diabetes mellitus - Gedam, Smruti; Ponde, Sanjay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Diabetes mellitus is the commonest medical problem complicating pregnancy, with possibility of grave consequences. With the present study, incidence, management and perinatal outcomes in the cases of GDM were studied. Methods: All the pregnant patients attending antenatal clinic at the study centre during study period of three years were studied. Those with positive history were screened for GDM as early as possible and rest screened at 24-28 weeks gestation. Carpenter and Coustan criteria were used for the diagnosis of gestational diabetes mellitus. All the diagnosed cases of gestational diabetes mellitus were followed up throughout the course of gestation and complications, if any, recorded. Results: A total of 39 patients were diagnosed as GDM. Majority were multigravida (69.3%, 27) and weighed over 75 kg (56%, 22). Patients were mostly diagnosed at the gestational age of 31-35 weeks (n-15) and 21-25 weeks (n-11). Fifteen patients (38.4%) had HbA1c values between 6-7%, 14 patients (35.8%) between 7-8% and 3 patients had HBA1c levels more than 10%. Twenty-three percent (9) patients had PIH, 13% (5) polyhydramnios and 7.6% (3) had PROM. Three mothers had babies suffering from IUGR. Sixteen (41%) had full term normal delivery while 2 (5.1%) patients had preterm labor and delivered normally. Twenty-one mothers (53.84%) had LSCS, out of which 3 had preterm LSCS. Conclusions: Diabetes during pregnancy is associated with risk factors as well as high maternal and foetal morbidity. GDM has good maternal and foetal outcomes depending upon how well the blood sugar levels are controlled.